THE DISTINCTIVE CHARACTERS OF THE NATIONAL LINGUISTIC WORLDVIEW ON THE EXAMPLE OF KARAKALPAK AND ENGLISH LANGUAGES - Muratbaeva Umida Taumuratovna (KONFERENSIYALAR, 2025)
Abstract. Current interested doubted issue in Linguistics is the national linguistic worldview that many cognitive linguists, ethnolinguistics, semiotics and philosophy of language are investigation both national and world linguistic worldview. In essence, the national linguistic worldview is a multidisciplinary concept that touches on how language shapes and depicts the cultural and mental framework of a nation or community. Every single word spoken by a nation shapes the basic understanding the nations’ notion for other language speakers, that is why it is essential to be aware the representation of linguistic worldview.